Community Service Monitoring Information System at The Level of Community Harmony of Citizens - Firera, Romario; Iskandar, Akbar (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
Effective and efficient public services are a fundamental requirement for improving the quality of interactions between citizens and government officials at the sub-district, village, and neighborhood association (RW) levels. Conventional, manual-based service systems often result in delays, long queues, and limited transparency. This study aims to design and build a web-based Community Association Service Information System at Perumnas Antang Blok 10 by adopting the System Development Life Cycle (SDLC) method as a system development framework, and the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method as a decision support tool in the social assistance acceptance process. The results show that the developed system is able to accelerate the reporting process, improve data accuracy, and provide services without having to go through a physical queue process. This system also provides significant benefits in supporting objective decision-making regarding the distribution of social assistance. Based on the results of a questionnaire trial involving respondents, a final score of 88% was obtained, indicating that the system is considered very good and feasible to use. These findings confirm that the innovation of the web-based public service information system not only improves the quality of services at the RW level but also contributes to the realization of more transparent, responsive, and accountable governance.